Desenvolvimento e otimização da produção de diésteres de etileno glicol (biolubrificantes) por hidroesterificação enzimática do óleo de fritura - José Geraldo Esteves Guedes Junior (2021)
The aim of this Dissertation (Master of Science) has been the production of na enzimatic biocatalyst capable of synthesizing diesters with lubricant properties (biolubricants) through hydroesterification of used soybean cooking oil – USCO (or waste cooking oil). The first step consisted in FFA production via enzymatic hydrolysis of USCO catalyzed by a crude lipase extract from Candida rugosa (CRL). Complete hydrolysis of the oils were achieved after 3 h of reaction at 40 °C, using 3.2 g/L of CRL, mechanical stirring frequency of 1500 rpm and oil:water mass ratio of 40% m/m. Next, the produced FFA have been separed, washed with distilled water and dehydrated to be used as starting materials in esterification step. In this study, the esters production has been performed in an eco-friendly process (solvent-free systems) and open reactors to eliminate formed water molecules in the reaction. In this step, a liquid lipase preparation from Thermomyces lanuginosus (Eversa® Transform 2.0)has been immobilized on poly(styrene-divinylbenzene) paarticles and it has been used as heterogeneous biocatalyst. The immobilization protocol proceeded by physical adsorption via mechanism of interfacial activation at low ionic strenght (5 mM) buffer sodium acetate pH 5.0 at 25°C, 18 h of contact under continuous mechanical stirring (200 rpm) in a controlled water bath temperature using an initial protein loading of 40 mg protein/g of support. High protein loaded biocatalyst around of 36 mg/g (immobilization of ≈90%) has been obtained due to high surface area and pore size of the support. In this study, four different glycols such as ethylene glycol (EG), propylene glycol (PG), diethylene glycol (DEG) and neopentyl glycol (NPG) were used as reactants in diesters production via esterification of the produce FFA using immobilized Eversa® Transform 2.0 as heterogeneous biocatalyst. Maximum OH conversion of 87% at 90 min of reaction was achieved using EG. Thus, further tests for optimizing the enzymatic esters production using statistical tools were performed with EG. The effect of three relevant parameters such as heterogeneous biocatalyst concentration, reaction temperature and EG:FFA molar ratio was evaluated using a full factorial design in a CCRD mode. Under optimal experimental conditions, the effect of contact time on the esters production hs also been evaluated. According to results, full OH conversion was achieved at 65 °C, EG:FFA molar ratio of 1:3, and biocatalyst concentration of 18% m/m at 40 min of reaction. Maximum OH conversion of only 32.5% was obtained using crude lipase extract under such conditions. The biocatalyst retained ≈37% of its original activity after seven successive esterification batches. The diesters production has been confirmed by proton nuclear magnetic resonance analysis (1H NMR). The physical properties of the produced diesters such as kinematic viscosity, visccosity index and pour point have been determined according to standard methods. Based on these results, kinematic viscosity values at 40°C and 100°C were 27.3 ± 1.6 e 5.7 ± 0.4 mm2/s. In addition, the viscosity index was of 166.2 ± 18.2. They presented good cold temperature properties, since its pour point was –9 ± 2°C. The physical properties of the produced diesters were comparable with EG diesters from soybean oils described in literature and comercial synthetic esters from two companies: Emery Oleochemicals (Dehylube® 4016 and Dehylube®4016 US) and Zschimmer & Schwarz (LEXOLUBE 3JN-310 and LUBRICIT NGDO). These results clearly show that the proposed process can be an interesting option in industrial processes due to its high catalytic activity under mild reaction conditions (65 °C and atmosphere pressure). Moreover, the physical properties of the produced diesters using a low-cost oleaginous feedstock, a waste oil from the food processing, were similar to commercial synthetic esters.